ANALISIS FAKTOR RISIKO KARAKTERISTIK, DAN PERSONAL HYGIENE DENGAN KEJADIAN PENYAKIT SKABIES PADA SANTRI DI PONDOK PESANTREN: META ANALYSIS TAHUN 2016-2021 - Mufidah, Imro’atul; Azizah, R.; Latif, Mohd Talib; Sulistyorini, Lilis; Yudhastuti, Ririh (Dian Nuswantoro Semarang, 2023)
Scabies is a significant disease for public health because it is a substantial contributor to global morbidity and mortality. The prevalence of scabies worldwide is reported to be around 300 million cases annually. The incidence of scabies in Indonesia is still very high and located in West java. The purpose of this study was to analyze the characteristic risk factors and personal hygiene, as well as to test the sensitivity of these risk factors to the incidence of scabies in Islamic boarding school students. The variable gender has a 2,117 times greater risk, knowledge has a 1,323 times greater risk, bathing habits have a 1.185 times greater risk, cleanliness of clothing has a 1,553 times greater risk of experiencing disease scabies. The results of the meta-analysis that has a greater level of risk in terms of characteristics is the gender variable and the personal hygiene variable that has a greater risk factor is the clothing cleanliness variable. Efforts that can be made by related agencies in the Pondok Pesantren area are to carry out promotive and preventive activities to prevent the occurrence of scabies in Islamic boarding schools.